Development of κ-Carrageenan Poly(acrylic acid) Interpenetrating Network Hydrogel as Wound Dressing Patch - Chakraborty, Soma (Archīum Ateneo, 2010)
Interpenetrating network (IPN) of κ-carrageenan and poly(acrylic acid) was fabricated. Polyacrylic acid was synthesized as well as crosslinked in the presence of κ-carrageenan followed by crosslinking the κ-carrageenan in the presence of sodium ion. In order to fabricate glycidyl trimethyl ammonium chloride(Quat 188) modified κ-carrageenan IPN, κ-carrageenan was first coupled with Quat 188 in the presence of base followed by the fabrication of IPN. Analysis of the DSC thermogram revealed that the rigidity of the IPN improved with the increment of the κ-carrageenan content. Modification of κ-carrageenan further increased the rigidity. The IPNs swelled almost 300% in aqueous medium to form the hydrogels. Swelling was more pronounced in basic pH than in acidic pH. These hydrogels could incorporate approximately 94% of the prototype drug AgNO3 in 30min from aqueous medium.